Arborização urbana como bioindicadora de poluição atmosférica : um estudo de caso com Moquilea tomentosa Benth. (Chrysobalanaceae) no Norte de Mato Grosso - Deecken, Bruna Paz (2021)
This study analyzed the presence of mercury in the atmosphere, through the evaluation of leaf samples of Moquilea tomentosa Benth. (Chrysobalanaceae), popularly known as “Oiti”, a tree species widely used in urban afforestation throughout Brazil. The study was carried out in 2020, in six municipalities in the northern region of Mato Grosso, inserted in the JuruenaTeles Pires Gold Province. In each municipality, triplicates of the leaves of 30 specimens of M. tomentosa were sampled, totaling 180 samples with approximately 200g each. The mercury content present in the samples was determined by atomic absorption spectroscopy, with atomization by cold vapor generation. Significant variation (ANOVA = p≤ 0.0001) was observed in the mean concentration of mercury among the six cities evaluated, showing the presence of this metal in the atmosphere in all areas. The highest mean Hg value was recorded in Paranaíta (172.8 µg Kg-1), followed by Alta Floresta (62.1 µg Kg-1), Carlinda (52.3 µg Kg-1), Nova Canaã do Norte (25.5 µg Kg-1), Colider (19.3 Kg-1) and Nova Santa Helena (6.8 µg Kg-1). The use of M. tomentosa is recommended as an indicator of atmospheric mercury deposition in urban areas, with the need for future studies following a time series aiming at establishing specific protocols for different types of atmospheric pollutants.